Safe Motherhood Practice in Dalit Community - Pasad, Subhash (Academic Voices: A Multidisciplinary Journal, 2013)
Safe motherhood practice is still poor among the unprivileged groups like the Dalit of Nepal. Low socio-economic condition and lack of awareness in the Dalit community seems to have negative impact on women health and safe motherhood practice. This paper describes the practice of safe motherhood in the Dalit community based on quantitative data collected from 120 mothers. The respondents were interviewed by using interview schedule. It is concluded that lack of education and awareness, low socioeconomic condition, teenage marriage and early pregnancy, improper antenatal care service, unsafe delivery at home, improper postnatal checkup and traditional attitudes indicate that safe motherhood practice is not satisfactory in the Dalit community. Academic Voices, Vol. 2, No. 1, 2012, Pages 63-68 DOI: http://dx.doi.org/10.3126/av.v2i1.8291